Calcium Phosphate Cement: Review of Mechanical and Biological Properties - Alberto J. Ambard, DDS, MS;1 and Leonard Mueninghoff, DDS2 (Journal of Prosthodontics, 2006)
Calcium phosphate cement is a bioactive and biodegradable grafting material in the form of powder and liquid, which when mixed, sets as primarily hydroxyapatite, sometimes mixed with unreacted particles and other phases.